Exciton diamagnetic shift in GaAs=Ga1xAlxAs quantum wells under in-plane magnetic fields (2008)
ABSTRACT: Using a variational procedure in the effective-mass and parabolic-band approximations we investigate the effects of in-plane magnetic fields on the exciton states in single quantum wells. Exciton properties are analyzed by using a simple hydrogen-like variational envelope wave-function. Present theoretical results are compared with available experimental measurements on the diamagnetic shift of the photoluminescence peak position of quantum wells under in-plane magnetic fields [Phys. Rev. B 71 (2005) 045303].